2004
DOI: 10.1039/b306684c
|View full text |Cite
|
Sign up to set email alerts
|

Multiple labelled nanoparticles for bio detection

Abstract: Remote nanoparticle detection is required for the development of in situ biological probes. Here we describe the labelling of silver nanoparticles to produce multiply coded particles which can be detected by surface enhanced resonance Raman scattering (SERRS). There is a potential for thousands of codes to be written and read without the need for spatial resolution of components of the code. The use of these systems in bioanlaysis and in situ detection is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 18 publications
(21 reference statements)
1
23
0
1
Order By: Relevance
“…This method was used for the identification of Saccharomyces cerevisiae, E. coli F-amp, and Bacillus subtilis. To find the potential applicability of confocal SERS for sensitive biological detection in a microfluidic channel, Docherty et al [100] have demonstrated simultaneous SERS detection of three dye-labeled oligonucleotides with E. coli sequences in a microfluidic channel. The narrow SERS signals, compared with broad fluorescence emission bands, enable the simultaneous detection of multiple analytes.…”
Section: Biological Analysis and Biomedical Diagnosticsmentioning
confidence: 99%
“…This method was used for the identification of Saccharomyces cerevisiae, E. coli F-amp, and Bacillus subtilis. To find the potential applicability of confocal SERS for sensitive biological detection in a microfluidic channel, Docherty et al [100] have demonstrated simultaneous SERS detection of three dye-labeled oligonucleotides with E. coli sequences in a microfluidic channel. The narrow SERS signals, compared with broad fluorescence emission bands, enable the simultaneous detection of multiple analytes.…”
Section: Biological Analysis and Biomedical Diagnosticsmentioning
confidence: 99%
“…Surface-enhanced Raman scattering (SERS), a technique with high spectral specificity, multiplex capabilities, and photostability [1][2][3], has been widely applied to chemical analysis, biological detection and medical diagnosis [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…SERRS can be used, for example, for labeling both fluorophores and non-fluorophores. To test the sensitivity of the assay, the detection of 3,5-dimethoxy-4-(6 0 -azobenzotriazolyl)-phenylamine anchored on an Ag nanoparticle surface was studied, indicating a detection limit of about 10 À10 M [63]. Carrageenan biopolymers have also been used as a template and as reduction agent for the synthesis of Ag metallic nanoparticles.…”
Section: Carrageenansmentioning
confidence: 99%